2017
DOI: 10.1007/s10113-017-1132-6
|View full text |Cite
|
Sign up to set email alerts
|

Using land use/land cover trajectories to uncover ecosystem service patterns across the Alps

Abstract: Managing multiple ecosystem services (ES) in agricultural landscapes is a challenging task, especially in regions with complex topographical and agro-ecological conditions. These challenges require ES assessment approaches that go beyond the case study level and provide multi-temporal information at a transnational level. We used a spatiotemporal approach to examine the impact of specific land use/land cover (LULC) trajectories on eight ES for the past 150 years. We show how a spatially explicit ES upscaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 60 publications
5
33
0
2
Order By: Relevance
“…This finding contrasted with that of Queiroz et al [13], who found substantial differences in the distribution of provisioning, regulating, and cultural ES. On Zakynthos only, provisioning ES was distributed differently in relation to the other two ES groups, supporting a study conducted to an Alpine-wide level [99], in which provisioning ES was found to be clustered in different areas to those where regulating and cultural ES occur. All three ES groups exhibited significant differences in their temporal variation over time in Corfu only, whereas provisioning ES and recreation followed a similar decreasing trend and regulating services increased.…”
Section: Mapping Ecosystem Servicessupporting
confidence: 71%
“…This finding contrasted with that of Queiroz et al [13], who found substantial differences in the distribution of provisioning, regulating, and cultural ES. On Zakynthos only, provisioning ES was distributed differently in relation to the other two ES groups, supporting a study conducted to an Alpine-wide level [99], in which provisioning ES was found to be clustered in different areas to those where regulating and cultural ES occur. All three ES groups exhibited significant differences in their temporal variation over time in Corfu only, whereas provisioning ES and recreation followed a similar decreasing trend and regulating services increased.…”
Section: Mapping Ecosystem Servicessupporting
confidence: 71%
“…Ecological functions and processes of ecosystems (ES supply) generate goods and services that are demanded by society (ES demand) (i.e., there is a directional flow from the ecosystems to the beneficiaries) [37,45]. The capacity of the ecosystems to provide ESs is influenced by environmental assets such as climate, land-use/cover and topography [45], but stakeholders and land managers may alter the ecosystems to increase the provision of desired ESs through environmental management [30,[46][47][48]. Actors of the SES with their social and economic relations determine furthermore the type and level of use of the ecosystems (ES flow) [10,49], which may result in an unequal distribution of ESs, or prevent people from having access to ESs.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Besides direct drivers, there are also indirect drivers of change due to socioeconomic pressures (e.g., population growth, demand for agricultural commodities, and pricing) that act simultaneously and can cause non-climatological drivers, for example, land cover and land use change. Land cover and land use change have been one of the most frequently studied non-climatological drivers with often negative impacts on ES (Polasky et al 2011, Lawler et al 2014, Egarter Vigl et al 2017.…”
Section: Introductionmentioning
confidence: 99%